2023
DOI: 10.1002/aur.2992
|View full text |Cite
|
Sign up to set email alerts
|

The developmental trajectory of functional excitation‐inhibition balance relates to language abilities in autistic and allistic children

Hannah Plueckebaum,
Lars Meyer,
Ann‐Kathrin Beck
et al.

Abstract: Autism is a neurodevelopmental condition that has been related to an overall imbalance between the brain's excitatory (E) and inhibitory (I) systems. Such an EI imbalance can lead to structural and functional cortical deviances and thus alter information processing in the brain, ultimately giving rise to autism traits. However, the developmental trajectory of EI imbalances across childhood and adolescence has not been investigated yet. Therefore, its relationship to autism traits is not well understood. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 94 publications
0
0
0
Order By: Relevance
“…Indeed, autistic children show differential development in EEG oscillations and non-oscillatory electrophysiological activity (Tierney et al, 2012), and these electrophysiological differences relate to language development (Romeo et al, 2021;Shuffrey et al, 2022;Wilkinson et al, 2020). In a recent study, it has been shown that the development of E/I imbalances across childhood and adolescence are associated with individual differences in listening comprehension in both autistic and non-autistic children (Plueckebaum et al, 2023). Additionally, there are some indications that the maturation of iAPF is atypical in autistic children (Edgar et al, 2019;Green et al, 2022;but see Carter Leno et al, 2021;Lefebvre et al, 2018).…”
Section: Implications For Atypical Language Acquisition -Autismmentioning
confidence: 99%
“…Indeed, autistic children show differential development in EEG oscillations and non-oscillatory electrophysiological activity (Tierney et al, 2012), and these electrophysiological differences relate to language development (Romeo et al, 2021;Shuffrey et al, 2022;Wilkinson et al, 2020). In a recent study, it has been shown that the development of E/I imbalances across childhood and adolescence are associated with individual differences in listening comprehension in both autistic and non-autistic children (Plueckebaum et al, 2023). Additionally, there are some indications that the maturation of iAPF is atypical in autistic children (Edgar et al, 2019;Green et al, 2022;but see Carter Leno et al, 2021;Lefebvre et al, 2018).…”
Section: Implications For Atypical Language Acquisition -Autismmentioning
confidence: 99%